Development of High Technologies as an Indicator of Modern Industry in the Eu - Gierańczyk, Wiesława (Bulletin of Geography. Socio-economic Series, 2010)
The article tries to classify the EU states in terms of the advancement of structural changes in their industries on the basis of the increase in the share of advanced technologies in total industrial production, labour, added value, and surplus. In the times of the knowledge-based economy the ability to produce high-tech goods, the demand for which is growing much faster than for traditional goods, indicates the level of modernity of industry. The dynamic growth of the demand for knowledge-based high-tech goods results from the evolution of consumer habits, which are predominantly driven by educated and rich societies who demand that their sophisticated needs met. An important role in stimulating this demand is played by modern media as they instantly deliver information on the latest technical developments and are very efficient in transferring patterns of consumerism. The ability to adapt the structure of production to the needs of the market is crucial in defining a state's position in the international exchange of goods. This is due to the fact that the national technology is tightly interwoven with export abilities.